2016
DOI: 10.4314/tjpr.v15i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect and Underlying Mechanisms of Total Triterpenoids from <i>Psidium guajava</i> Linn (Myrtaceae) Leaf on High-Fat Streptozotocin-induced Diabetic Peripheral Neuropathy in Rats

Abstract: Purpose: To investigate whether the total triterpenoids extracted from Psidium Guajava leaves (TTPGL) attenuate the development of diabetic peripheral neuropathy in rats by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…IL-β1, TNFα, and PGE2 were decreased in gene expression when cells were exposed to the combination of guava and LPS (Figure 2). Our findings corroborate previous studies that confirmed guava extract to be a powerful anti-inflammatory agent [19,36,37]. The inflammation inhibitory effect was found to be closely linked to the phenolic and flavonoid content of the guava extract [38,39].…”
Section: Discussionsupporting
confidence: 92%
“…IL-β1, TNFα, and PGE2 were decreased in gene expression when cells were exposed to the combination of guava and LPS (Figure 2). Our findings corroborate previous studies that confirmed guava extract to be a powerful anti-inflammatory agent [19,36,37]. The inflammation inhibitory effect was found to be closely linked to the phenolic and flavonoid content of the guava extract [38,39].…”
Section: Discussionsupporting
confidence: 92%
“…Triterpenoids from guava leaves were suggested as a potential therapeutic approach for treating diabetic peripheral neuropathy, as they enhanced physical functions and offered neuronal protection towards the suppression of the expression of pro-inflammatory cytokines [ 139 ]. In addition, the leaves can act as radio modulators for cancer patients because by preventing DNA damage and apoptosis.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Triterpenoids are the major components in the leaf of P. guajava. The total triterpenoids could ameliorate the development of diabetic peripheral neuropathy in rats, and improved insulin resistance in 3T3-L1 adipocytes [12,13]. Corosolic acid, the major triterpenoid in the leaf, is a very potent α-glucosidase inhibitor.…”
Section: Introductionmentioning
confidence: 99%